Studi Perbandingan Bahan Bakar Minyak Dengan Bahan Bakar Gas LPG (Liquified Petroleum Gas) Terhadap Konsumsi Bahan Bakar Sepeda Motor 4 Tak 125 CC - Windia Pebrianto; Husin Bugis; Ranto Ranto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
Liquified Petroleum Gas is a gaseous hydrocarbon produced from gas and oil with the main components being propane and butane. The use of LPG gas fuel was chosen because it is able to reduce the amount of fuel consumption by up to 30% more efficient than fuel oil in general. The use of LPG fuel can be optimized by modifying the size of the pilot jet, the size of the main jet and the gas flow valve opening on the regulator. The purpose of this study was to investigate how big the ratio of fuel consumption between LPG fuel and pertalite fuel is. This study used Honda Supra 125 D as a sample. The variables used in this study include: variations in the size of the pilot jet (40, 42, 45), variations in the size of the main jet (72, 98, 120) and the gas flow valve opening on the regulator (10%, 15%, 20%). The results showed that the lowest LPG fuel consumption value was obtained at 156.5 grams per 10 kilometers, while the pertalite fuel consumption value was obtained at 232.9 grams (after converting from liters to grams). The most influential factor is the replacement of the main jet size on the use of LPG fuel.